Mandado de segurança no âmbito tributário: perspectiva constitucional dos efeitos patrimoniais pretéritos - Carvalho, Roberta Vieira Gemente de (2024)
This work seeks to identify the real contours of the practicability and effectiveness of the Writ of Mandamus in the tax sphere, aiming to restore its constitutional fullness by elucidating the misinterpretations about the limits of Precedents n.º 269 and 271 of the Federal Supreme Court, in addition to harmonizing its system and procedures with the new procedural provisions brought in by Federal Law n.º 13.105 of 16.03.2015. To this end, the jurisprudence that formed the aforementioned precedents, legislation and doctrine was critically revisited, demonstrating the renewal and evolution of the legislation governing the writ of mandamus and the establishment of a new procedural order with the advent of the 2015 Code of Civil Procedure, extinguishing the autonomous enforcement process based on a judicial enforcement order, making the judgment that declares the right an immediate cause for enforcement in the case itself, demanding an effort to review the theses established until then. Through a critical and systemic analysis of the elements mentioned above, it became clear that the application of Precedents 269 and 271 of the Supreme Court to the tax sphere entails illegitimate restrictions on the writ of mandamus, reducing its field of action clearly defined by the Federal Constitution. The result of this work leads to an understanding of the origins of the limitations established by the Precedents dealt with, bringing interpretative premises that guarantee their maximum applicability, as well as proving the legality of producing past patrimonial effects, through execution in the records themselves, without the denaturation of the writ